An Ethnographic Exploration of Performance-Based Learning in Chinese University Music Education - Zhang, Shuai (Pacific International Journal, 2024)
This ethnographic study explores the impact of performance-based learning on music education at Langfang Teachers University in China. Through observations and interviews, the study examines how live demonstrations, student performances, and ensemble practices contribute to students’ technical proficiency, musical interpretation, collaborative skills, and self-confidence. The findings reveal high levels of student engagement and appreciation for hands-on learning, with significant improvements in instrumental and vocal skills. However, challenges such as performance anxiety, resource limitations, time management issues, and varying levels of preparedness were also identified. Recommendations include implementing workshops for anxiety management, increasing funding for facilities, developing structured practice schedules, and introducing peer mentoring programs. The study underscores the importance of integrating traditional Chinese music with contemporary practices, ensuring a well-rounded and culturally enriched music education that prepares students for diverse careers in the global music industry.